Two new Orthoseira species (Bacillariophyceae) from lava tubes on Île Amsterdam and Big Island (Hawai΄i) - Lowe, Rex L.; Kociolek, J. Patrick; de Vijver, Bart Van (Phytotaxa, 2013)
Two new species of Orthoseira from lava tubes on Île Amsterdam and Big Island (Hawai΄i) are described using light and scanning electron microscopy: Orthoseira johansenii Lowe & Kociolek sp. nov., from Hawai’i, and O. verleyenii Van de Vijver sp. nov., from the subantarctic. Both species have flat valve surfaces, the striae on the mantle are composed of uniseriate areolae and the valve face areolae are small and more or less irregularly scattered, occupying almost 2/3 of the total valve face surface. The areolae in O. johansenii are occluded by an internal velum; no velum was detected in O. verleyenii. In the centre of the valve is a small central hyaline area with 1–6 carinoportulae in O. verleyenii, 2–4 in O. johansenii. A distinct ring of marginal linking spines or straight, non-linking spines are present at the valve face/mantle junction. No caverns or internal undulations are present. Internal valves have not been encountered. Both Orthoseira johansenii and O. verleyenii have valves of about the same dimensions. The two species differ in that O. verleyenii shows a rather regular striation pattern near the valve face/mantle junction is noted whereas this is not the case in O. johansenii. Moreover, O. johansenii short slits between the carinoportulae on the internal valve side are absent whereas in O. verleyenii most valves possesses these slits. The two new species are compared with others in this small (ca. 15 species) genus. The biogeographic implications of species separated by 15,000 km are discussed.